Blood monocyte activation in rheumatoid arthritis: increased monocyte adhesiveness, integrin expression, and cytokine release - LIOTÉ, F.; BOVAL‐BOIZARD, B.; WEILL, D.; KUNTZ, D.; WAUTIER, J.‐L. (Clinical and experimental immunology, 1996)
Infiltration of the synovium by mononuclear cells, namely lymphocytes and monocytes, is one of the main features of rheumatoid arthritis (RA) and is considered to be responsible for the development of the disease. In this study in 31 consecutive patients with RA, we investigated whether peripheral blood monocytes exhibited markers of cellular activation related to cell migration. Using flow cytometry with the respective specific antibodies, we studied the expression of integrins CD11a, CD11b, CD11c, CD49d (VLA‐4), and CD49e (VLA‐5) on monocytes from patients with RA and from normal (N) subjects. IL‐1β, IL‐6, and tumour necrosis factor‐alpha (TNF‐α) production by cultured monocytes was measured by immunoassay. Adhesiveness of monocytes was studied on various surfaces (plastic, human fibronectin, gelatin‐coated plasma, subendothelial matrix) and on cultured endothelial cells under basal conditions or after stimulation by IL‐1β. An increased number of CD14+ monocytes (Mo) from RA patients expressed the CD11b molecule (RA Mo = 90.3%, N Mo = 83.4%, P < 0.005). The expression of CD11b on CD14+ monocytes was significantly increased in RA patients (median fluorescence intensity (FI): RA Mo = 145 (range 80–466) units; normal Mo = 95 (range 24–164) units; P < 0.003). Production of extracellular IL‐1β and IL‐6 by RA monocytes was significantly enhanced compared with monocytes from normal subjects (IL‐1β : RA = 2.65 ± 0.91 ng/ml versusN = 1.35 ± 0.85 pg/ml, P < 0.05; IL‐6: RA = 4.83 ± 0.90 ng/ml versusN = 2.40 ± 0.95 ng/ml, P < 0.05). Compared with normal monocytes, RA monocytes exhibited increased adhesion to the various surfaces studied (plastic, P < 0.01; fibronectin, P < 0.01; and gelatin‐coated normal or RA plasma, P < 0.01) as well as to unstimulated (P < 0.01) and IL‐1β‐stimulated endothelial cells (IL‐1β for 4 h, P < 0.05; IL‐1β for 24 h, P < 0.05). In our study, blood monocytes from RA patients exhibited features of activation related to cell adhesion.